2022
DOI: 10.2478/hepo-2022-0003
|View full text |Cite
|
Sign up to set email alerts
|

Study of total antioxidant activity of green tea leaves (Camellia sinensis L.)

Abstract: Summary Introduction: There is a high interest in creating medicines, dietary supplements, cosmetics including plant extract with antioxidant activity. For understanding whether plant extract has a maximum level of antioxidant activity it is important to know the total antioxidant activity of raw material. Objective: The main goal of study was to find out the green tea leaves total antioxidant activity. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 28 publications
1
18
0
6
Order By: Relevance
“…16 The presence of phytochemicals indicates a main role in the antioxidant activity. 17 The antibacterial property of the different wild tea leaves' extracts against E. coli coincides with the finding of Tarnam 18 wherein Clausena sp. showed a maximum zone of inhibition against E. coli.…”
Section: Discussionmentioning
confidence: 82%
“…16 The presence of phytochemicals indicates a main role in the antioxidant activity. 17 The antibacterial property of the different wild tea leaves' extracts against E. coli coincides with the finding of Tarnam 18 wherein Clausena sp. showed a maximum zone of inhibition against E. coli.…”
Section: Discussionmentioning
confidence: 82%
“…The total content of phenolic compounds was measured via Folin-Ciocaltau assay, the optical density was measured at 760 nm [10]. The calibration curve was plotted with interval concentrations 1.0-5.0 μg/ml, the calibration equation being Y = 0.1055X + 0.1745 (R 2 =0.9951) expressed as gallic acid and calculated according to the following equation:…”
Section: Qualitative Analysismentioning
confidence: 99%
“…Antioxidant activity (AOA) of the extract was evaluated by utilizing the potentiometric method [15,16], and was calculated according to the following equation and expressed as mmol-equiv./m dry res. :…”
Section: Antioxidant Activity Assaymentioning
confidence: 99%
“…The defense system of the human body involves endogenous enzymes inactivating ROS. The members of this group are superoxide dismutase, catalase, and glutathione peroxidase [3]. However, there are cases when the endogenous defense system is exhausted by chronic diseases, stress, and not a good diet.…”
Section: •-mentioning
confidence: 99%
“…However, no one has previously described the determination of the extraction frequency by measuring the antioxidant activity of the extracts. Our recent study [3] has revealed that 60 % ethanol is the optimal solvent for obtaining an extract from green tea leaves. Therefore, the current work aimed to study the dynamics of extraction of biologically active substances from green tea leaves with 60 % ethanol to determine the optimal extraction frequency by the method of measuring the antioxidant activity.…”
Section: •-mentioning
confidence: 99%